KETERLIBATAN ORANG TUA DALAM PELAKSANAAN PENDIDIKAN AGAMA ISLAM DALAM RUMAH TANGGA DI DESA TAMBANGAN, KECAMATAN KAJANG, KABUPATEN BULUKUMBA - B., Chaeruddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
The research conducted in Tambangan village of Kajang district was directed to gain objective description on household base involvement of parents towards Islamic education adminis-tration. The data collection was done under the intensive observation and interview to all respondents. The result of this research showed that: Most of parents didn’t do direct involvement in Islamic edu-cation administration in their family. They delegated that self invol-vement to the teachers of religion subjects in the school and/or institute for Qur’anic education (TPA)/Qur’anic kindergarten (TKA) in stead. The parents who took direct involvement in Islamic edu-cation administration apply habit formation, giving advice, noble characters methods in terms of Islamic orders and prohibition. They also used traditional approach and method (Al-Bagdadi) particularly applied in Quranic writing and recitation education.